One-click content, no guarantees [online encyclopedia reliability]. - Svoboda, E.
As the first-ever major reference work with a democratic premise, the free online encyclopedia, Wikipedia, has generated shared scholarly efforts to rival those of any literary or philosophical movement in history. As such, Wikipedia is vulnerable to user-generated articles that are inaccurate or irrelevant. While a carefully executed and multilayered review process is performed by a team of volunteers, critics believe that the lack of formal gatekeeping procedures ensures that the lowest common denominator will prevail and, since no experts or editors are hired to review the articles, no clear standards exist for accuracy or writing quality. Despite its imperfections, Wikipedia users claim that it works well in practice. Nevertheless, readers are advised to check their online finds against other sources and to be aware of Wikipedia's unique strengths and weaknesses, especially when gathering information for research projects.
Keywords: Wikipedia; Information gathering; Multilayered review process; Online encyclopedia reliability; User-generated encyclopedia